Clinical benefits from endoscopy screening of esophageal second primary tumor for head and neck cancer patients: Analysis of a hospital-based registry - Chung, Chen-Shuan; Lo, Wu-Chia; Chen, Kuan-Chih; Lin, Cheng-Lu; Wen, Ming-Hsun; Hsieh, Chen-Hsi; Lin, Shih-Chiang; Liao, Li-Jen (Oral oncology, 2019)
•Esophageal neoplasia is not uncommon in head and neck caner (HNC) patients.•Survivals of HNC patients without esophageal neoplasia after screening are better.•Endoscopy screening of esophagus is crucial for HNC patients' prognosis prediction. Esophageal second primary tumors (SPTs) in head and neck cancer (HNC) patients is not uncommon. The impact of image-enhanced endoscopy (IEE) screening for esophageal SPT on the outcome of HNC patients has not been well clarified. Patients with malignancies of the head and neck region and esophagus were recruited from a hospital-based cancer registry between July 2000–December 2016. IEE screening included magnifying endoscopy with narrow-band imaging and chromoendoscopy with Lugol's solution. Biopsied specimens with revised Vienna classification categories 1 and 2 were defined as group I, and those with categories 3 to 5 were defined as group II. The Kaplan-Meier estimate and Cox regression model were used for survival analysis. Totally 1577 HNC and 501 esophageal cancer patients were enrolled. The 5-year overall survival (OS) rates of stage I/II HNC, stage III/IV HNC and esophageal cancer patients were 58%, 29%, and 8%, respectively (p < 0.01). The 5-year OS rate of HNC patients with negative IEE results was higher than that of HNC patients without IEE screening, followed by IEE screening groups I, II and esophageal cancer patients (44% vs. 39% vs. 35% vs. 11% vs. 8%, respectively, p for trend <0.01). Among advanced HNC patients, those who received IEE screening had a trend of better prognosis than those without screening (5-year OS rate of 31% vs. 28%, p = 0.17). IEE screening for esophageal SPTs is helpful in risk stratification and prognosis prediction for HNC patients. Routine IEE screening is recommended in HNC patients.